Performers and researchers in neo-pagan settings - Velkoborská, Kamila (Traditiones (Ljubljana), 2012)
In neo-pagan and magical settings, the traditional distinction between the anthropologist and the "others" disappears due to the fact that researchers and performers tend to have the same ethnic background, social position, and level of formal education. Author has identified main approaches towards magic used by anthropologists.
Keywords: ethnology; Etnologija; Verovanje; Magija; magic; ljudska verovanja; ljudski obredi; ljudski običaji